Ultrastructural changes of chorioretinal complex under sub-threshold laser exposure at wavelengths of 0.81 and 0.532 μm (experimental study) - N. A. Fedoruk; A. A. Fedorov; A. V. Bolshunov (Oftalʹmologiâ, 2015)
Aim: To reveal ultrastructural changes of chorioretinal complex and their possible reversibility under sub-threshold laser exposure at wavelengths of 0.81 and 0.532 μm in 1, 8 and 30 days. Methods: Experimental study was performed on 16 chinchilla rabbits (32 eyes) using laser at wavelengths of 0.532 and 0.81 μm in CW, micropulse, and transpupillary thermotherapy modes. Transmission electron microscope EM-10C (Opton, Oberkochen, Germany) was used to perform ultrastructural study of retina following laser exposure. Results: In a day after sub-threshold laser exposure, ultrastructural changes were mainly detected in retinal pigment epithelium (RPE), choriocapillaries, and photoreceptors. In 8 days, intracellular regeneration of RPE and partial restoration of choriocapillary blood flow and RPE macrophages were observed. In 30 days, RPE morphology, the number and the structure of photoreceptor outer segments were re-established. Mitochondria of photoreceptor inner segments regenerated as well. Conclusion: Ultrastructural changes of chorioretinal complex following sub-threshold laser radiation were reversible. Intracellular regeneration provided almost complete recovery of chorioretinal complex structure by day 30.